A methodology to design a domotics human-machine interface for visually impaired people - Corrêa, Mayra; Llanos , Carlos; da Silva, Jones Y.; Raposo, Patrícia Neves; Munoz, Ivette Kafure (Revista Interdisciplinar de Pesquisa em Engenharia, 2022)
According to the World Health Organization (WHO), more than one billion people in the world have some disability. A 2017 report of the Brazilian Geography and Statistics Institute (IBGE) shows that 45.6 million Brazilians have an impairment, among which 18.8 million declare vision issues not fixed by glasses or contact lenses. So, a significant population leads to developing many legal mechanisms to guarantee their quality-of-life. Potentially, these mechanisms should regulate many aspects of urban design to assure the accessibility of any environment. However, there are several design challenges to be overcome. In this paper, we address the problem of developing Human-Machine Interfaces (HMI) for visually impaired people, focusing on residential automation systems (domotics). The efficient development of such interfaces needs a link among two accessibility areas: domotics and HMI. We used pre-tests, human-computer interaction (HCI) techniques, and the user's emotional state identification to determine the user's profile. We must highlight that the design is intended to be used by any user, visually impaired or not. That is, the system should be universal. The methodology described can be used to assess the efficiency and quality metrics of accessibility in domotics systems.